(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
As renewable raw material flax increasingly gain more importance as the range of its use is spreading more and more. Besides the conventional uses in home textiles, clothing and sails products, demand of flax raw materials for technical uses increases rapidly as flax fibers have high specific properties, become components of biodegradable composites, environmental friendly isolation materials, besides flax shives pay attention as well as components of environment friendly building materials. Unfortunately in Latvia during last decades flax crop production had decreased rapidly and nowadays reintroduction of flax growing traditions and conditions are become more and more actual. In spite of depression in sector, in Agriculture Science Centre of Latgale are not interrupted experiments on development of local flax lines. Field trials were sown at the Centre in 2010 and 98 flax lines investigated. In this article reflected analysis results of one perspective local fibers flax line from different aspects and its properties comparison with the standard fibers flax variety Vega 2.